Factors of customer satisfaction in different service industries / Sarah Sabir Ahmad ... [et al.] - Sabir Ahmad, Sarah; Zakaria, Azfahanee; Mat Seman, Mhd Azmin (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
RobertsLombard and Petzer (2017) declared that customer satisfaction is a way a product or service can meet or surpass the expectation of customers. Exceeding improving product and service quality and delivery can be a valuecustomer expectations by adding tool to customer satisfaction. Therefore, if an organization can provide value to the customers and meeting their needs, it is likely to be more effective in achieving or surpassing their expectations (Yeh, 2016).